We are given
An exponential function f(x) is reflected across the y-axis to create function g(x)
we know that whenever we have to reflect any function about y-axis , we will always replace x as -x
so, we reflect f(x) about y-axis
so, we can replace x as -x
we get new function as
f(-x)
and that is g(x)
so, we get
g(x)=f(-x)
Initial value means value of function at x=0
so, we will plug x=0
we get
g(0)=f(-0)
g(0)=f(0)
we can see that both f(x) and g(x) have same initial value
so,
The two functions have the same initial value............Answer